Constructing some possibilities for compensation as part of legal remedies for rape survivors: the case of Malaysia - Ismail, S.Z. (EuroJournals Publishing Inc.2011, 2011)
The idea of compensating rape victims is fast gaining momentum around the globe amidst the cry to seek justice for crime victims in general. Several NGOs in Malaysia see the importance of setting up an agency to response to the plight of these women. The law is seen as inadequately responsive towards the victims. Even by imposing stiffer punishment on the rapists, this does not bring any good to the victims. Some are left with various physical injuries, contracting sexually-related diseases and unwanted pregnancy, but almost all find it hard to overcome the psychological trauma, the effects that are more difficult to recognize than physical hurt. This study examines why compensation for rape victims is significantly necessary after the incident. The writer is of the opinion that compensation is one of the reparation possibilities and the relevant authority should not overlook the compensation probability to address the plight of the victims.